(3WHbGJ GdMfajIs - (3eMeO Gejf Hf MHjH GHf CHj HcQ Hf NVQ GdRjdj, eMeO Gejf GafOj RGOg HGcjs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf ai WHbGJ GUMGH GeGefG CHj MfjaI GdfYeGf Hf KGHJ QMeg Gddg QMeI hGSYI Ydi eG MQQg ehdGfG GdYGde GdeMbb GdeObb QajY GdOjf GdTQhGfi s
(3BNQgG (B:s
(3hdGOI GdTQja HQcGf SfI (B1034 (3hhaGJg ai (B28 (3QHjY GdBNQ SfI (B1093 (3fbd TjNfG GdeQMhe eMeO Gejf GafOi HGci RGOg s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B(7162) s
Keywords: (3eJaQbGJs